2024
DOI: 10.1111/cobi.14209
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interactive effects on long‐term population trajectories in multispecies reintroductions

Katherine E. Moseby,
John L. Read,
Katherine Tuft
et al.

Abstract: Reintroduced populations are typically considered to progress through establishment, growth and regulatory phases. However, most reintroduction programs don't monitor intensively enough to test this conceptual model. We studied population indices derived from track activity of four IUCN‐listed species (greater bilby, burrowing bettong, greater stick‐nest rat and Shark Bay bandicoot) over 23 years after multiple reintroductions of each species in arid Australia. We compared population trajectories between speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This suggests that the population abundance of S. douglasi at Bladensburg National Park fluctuates dramatically (more than tenfold), and this may be due to changes in rainfall, vegetation cover, food availability and formation of cracks for refuge (Mifsud, 1999 ). Fluctuating small mammal populations are not unusual in Australia (Moseby et al., 2023 ; Predavec & Dickman, 1994 ; Smith, 2015 ). However, if exacerbated by threats (e.g., climate change and feral predators), such dramatic fluctuations may be of conservation concern.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the population abundance of S. douglasi at Bladensburg National Park fluctuates dramatically (more than tenfold), and this may be due to changes in rainfall, vegetation cover, food availability and formation of cracks for refuge (Mifsud, 1999 ). Fluctuating small mammal populations are not unusual in Australia (Moseby et al., 2023 ; Predavec & Dickman, 1994 ; Smith, 2015 ). However, if exacerbated by threats (e.g., climate change and feral predators), such dramatic fluctuations may be of conservation concern.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of founders to develop effective behavioural responses to the release environment can rapidly lead to reintroduction failures (Moseby et al 2016;West et al 2018;Ross et al 2019). Post-release monitoring is therefore critical in the early stages of a reintroduction project, to determine whether founders have successfully adapted to their new environment, while also providing invaluable information for future reintroductions (Armstrong and Seddon 2008;Hayward et al 2015;Watkins et al 2018;Berger-Tal et al 2020;West et al 2020;Moseby et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from previous reintroductions suggests that bilbies can adapt to a range of environments and successfully establish populations, particularly in the absence of feral predators (Moseby and O'Donnell 2003;Berris et al 2020a;Moseby et al 2023). Post-release monitoring of bilbies reintroduced to an exclosure in arid South Australia showed that founder mortality rates were low and reproductive output was high, despite prior landscape degradation by domestic stock and feral species (Moseby and O'Donnell 2003).…”
Section: Introductionmentioning
confidence: 99%